Putuvaiyil Pāratiyār - Vēlāyutaṉār, Mu. Ta (Vāṉati, 1982)
Life and works of Pāratiyār, 1882-1921, Tamil litterateur and Indian freedom fighter; a study in the context of the influence of his 10-year-long stay in Pondicherry.